2021
DOI: 10.3233/jpd-212553
|View full text |Cite
|
Sign up to set email alerts
|

Negative Effects of COVID-19 Stay-at-Home Mandates on Physical Intervention Outcomes: A Preliminary Study

Abstract: Background: Due to the COVID-19 pandemic, beneficial physical intervention classes for individuals with Parkinson’s disease (PD) were cancelled. Objective: To understand effects of the COVID-19 stay-at-home mandate and the inability to participate in recommended and structured physical interventions as a consequence of these mandates, specifically designed mobile assessments were used that collected both self-reporting information and objective task-based metrics of neurocognitive functions to assess symptom c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…As physical daily activities and other contributing factors have not been measured in these patients, the study does not prove a causal link between confinement-dependent factors such as psychiatric status, activity level and worsened progression in PD. There is, however, evidence from qualitative studies suggesting an interrelation between physical activity and disease progression [14,17,19] and quantitative evidence that physical activity was significantly decreased during the stay-at-home mandate in PD-patients [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As physical daily activities and other contributing factors have not been measured in these patients, the study does not prove a causal link between confinement-dependent factors such as psychiatric status, activity level and worsened progression in PD. There is, however, evidence from qualitative studies suggesting an interrelation between physical activity and disease progression [14,17,19] and quantitative evidence that physical activity was significantly decreased during the stay-at-home mandate in PD-patients [5].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, data shows that COVID-19-dependent restrictions have negative effects on mental health [3] besides correlative evidence showing a worsening of non-motor features and potentially exacerbated motor symptoms in PD [4]. Further, a recent pilot study including mobile assessments to collect self-report data showed that it was physical activity that led to highest self-satisfaction in PD-patients during COVID-19 restrictions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the marked disturbances in the sleep/wake circadian rhythm as well as the behavioral changes in the home confinement period, determined the progressive decline in quality of lifestyle, satisfaction and mental wellbeing as affective disorders with depression, sadness, anxiety and feelings of loneliness that reflected lack of socialization from organized communities to emotional rehabilitation programs [40,41]. In addition to COVID-19 as a secondary stressor to the primary stressor, cognitive dysfunction, negative emotions, frustration and mental disorders had been exacerbated.…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary study on the stay at home mandate, a self-questionnaire was carried out with 36 patients by mobile based-neurocognitive assessment with PD, of which 53.6% were female and 46.4% were male, regarding physical activity/week, number of active days and average time allocated for physical exercise. Motor and neurocognitive patterns were quantified and performed by using the scales: MTA, MCA, NFI, SWCT and MMSE, which found decreases in motor skills, speech neurocognitive tasks and wellbeing life quality in approximately 80% of the patients with PD [40].…”
Section: Tools/variables Which Quantify Motor and Emotional Status At...mentioning
confidence: 99%
See 1 more Smart Citation